Cultural Influences on International Capital Structure - Sekely, William S.; Collins, J. Markham (Journal of International Business Studies, 1988)
Many studies have been conducted on the impact of various factors on international capital structure. The literature still reveals disagreement on the significance of the industry and country effects in determining capital structure, and the basis of country differences. This paper presents the results of a study of the debt structure of 677 firms in 9 industries headquartered in 23 countries. The results of this study tend to agree with the hypothesis that cultural differences are correlated with the significant country and minimal industry influences which are found. Further, there appear to be some intercountry influences caused by underlying cultural patterns among groups of countries.